Arabidopsis ADF5 Acts as a Downstream Target Gene of CBFs in Response to Low-Temperature Stress - Zhang, Pan; Qian, Dong; Luo, Changxin; Niu, Yingzhi; Li, Tian; Li, Chengying; Xiang, Yun; Wang, Xinyu; Niu, Yue (Frontiers in Cell and Developmental Biology, 2021)
Low temperature is a major adverse environment that affects normal plant growth. Previous reports showed that the actin cytoskeleton play an important role in the plant response to low-temperature stress, but the regulatory mechanism of the actin cytoskeleton in this process is not clear. C-repeat binding factors (CBFs) are the key molecular switches for plants to adapt to cold stress. However, whether CBFs are involved in the regulation of the actin cytoskeleton has not been reported. We found that Arabidopsis actin depolymerizing factor 5 (ADF5), an ADF that evolved F-actin bundling function, was up-regulated at low temperatures. We also demonstrated that CBFs bound to the ADF5 promoter directly in vivo and in vitro. The cold-induced expression of ADF5 was significantly inhibited in the cbfs triple mutant. The freezing resistance of the adf5 mutant was weaker than that of wild type（WT）with or without cold acclimation. After low-temperature treatment, the actin cytoskeleton of WT was relatively stable, and the actin cytoskeletons of adf5, cbfs and adf5cbfs were disturbed to varying degrees. Compared to WT, the endocytosis rate of the lipophilic dye FM4-64 in adf5, cbfs and adf5cbfs at low temperature was significantly reduced. In conclusion, CBFs directly combined with the CRT/DRE DNA regulatory element of the ADF5 promoter after low-temperature stress to transcriptionally activate the expression of ADF5; ADF5 further regulates the actin cytoskeleton dynamics to participate in the regulation of plant adaptation to a low-temperature environment.